1991
DOI: 10.1177/00220345910700111201
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Resin Components on Cultured Mammalian Fibroblasts

Abstract: The objectives of this study were to determine the cytotoxic concentrations of 11 components of resin composites on monolayers of cultured Balb/c 3T3 fibroblasts, to study the inhibitory effects of these components on DNA synthesis, total protein content, and protein synthesis, and to determine whether effects were reversible when the components were withdrawn from the medium. These data were reported as concentrations which inhibited 10% (ID10) and 50% (ID50) of a particular metabolic process as well as the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
239
1
13

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(279 citation statements)
references
References 22 publications
20
239
1
13
Order By: Relevance
“…Viability decrease caused by MTA Fillapex exceeded 75% when pure and ½ diluted. The addition of components in MTA Fillapex, such as resins (8), bismuth oxide (9) and other pigments, may have increased the toxic effect of this sealer compared to its precursor, MTA. In a recent study using osteoblast culture, Scelza et al (15) also observed significant cytotoxic levels for MTA Fillapex extracts, when prepared 1 or 7 days after the sealer manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viability decrease caused by MTA Fillapex exceeded 75% when pure and ½ diluted. The addition of components in MTA Fillapex, such as resins (8), bismuth oxide (9) and other pigments, may have increased the toxic effect of this sealer compared to its precursor, MTA. In a recent study using osteoblast culture, Scelza et al (15) also observed significant cytotoxic levels for MTA Fillapex extracts, when prepared 1 or 7 days after the sealer manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike regular MTA, MTA Fillapex was developed as a paste/paste sealer in a formulation that allows its appropriate insertion into the root canal as a conventional endodontic sealer (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been largely reported that HEMA induces apoptosis in vitro after 24 h (Table 3) (Hanks et al 1991, Krifka et al 2012. Moreover, HEMA induces morphological changes in cultured cells, such as human pulp fibroblasts (HPFs) and human gingival epithelial cells.…”
Section: Hema-induced Apoptosis In Vitromentioning
confidence: 99%
“…This view has been supported also by the fact that various components of dentine-bonding agents and restorative resin materials are directly toxic to cells [12,14,15]. Dentine conditioning agents can also be harmful when the pH value is lower than 5.5 and when they approach or come in contact with pulp [16].…”
Section: Introductionmentioning
confidence: 99%